## Examnut Latest Questions

Solution: 3x – 5 + 23x – 9 = 3x + 23x – 5 – 9 = 26x – 14 = 2(13x – 7) So Answer Is = 2(13x – 7)

Solution: 5 – 2 [8 – (2 x 2 – 4 x 4)] = 5 – 2 [8 – (4 – 16)] = 5 – 2 [8 – (-12)] = 5 – 2 [8 + 12] = 5 – 2 [20] = 5 – 40 = -35 So ...

Solution: (3 x 105) (3 x 103) = 9×105 + 3 = 3 × 3 × 105 × 103 = 9 × 108 So Answer Is = 9 × 108

Solution: 5.347 x 10-8 = 5.347/100000000 = 0.00000005347 So Answer Is = 0.00000005347

Solution: 0.000000373 = 3.73 × 10-7 So Answer Is = 3.73 × 10-7

Solution: x + y = 2 x + y – 2 = 0 Distance from (2, 3) to the line x + y – 2 = 0 = (2 + 3 – 2)/√(12 + 12) = 3/√(1 + 1) = 3/√2 = (3 × √2)/(√2 × √2) = (3√2)/2 ...

Solution: x + 4y = 7 4y = -x + 7 y = (-1/4) x + 7 Slope of the equation x + 4y = 7 is -1/4. Again, 4x – y = 3 y = 4x – 3 Slope of the equation 4x – y = ...